2016
DOI: 10.1111/joa.12466
|View full text |Cite
|
Sign up to set email alerts
|

A morphological adaptation? The prevalence of enlarged external occipital protuberance in young adults

Abstract: Enthesophytes are bony projections that arise from the sites of ligament, tendon or joint capsule attachment to a bone. They are seen rarely in radiographic findings in young adults, as these bony adaptations are assumed to develop slowly over time. However, in recent years, the presence of an enlarged external occipital protuberance (EEOP) has been observed frequently in radiographs of relatively young patients at the clinic of the lead author. Accordingly, the aim of this project was to assess the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…There are three types of EOP depending on its shape 2,3 : "flat type" (type 1), "crest type" (type 2) and "spine type" (type 3). Previous studies have shown that type 1 was more frequent in women and type 3 more frequent in men 2,4 . Type 3 can sometimes manifest as a subcutaneous scalp pseudotumor 5 .…”
mentioning
confidence: 87%
“…There are three types of EOP depending on its shape 2,3 : "flat type" (type 1), "crest type" (type 2) and "spine type" (type 3). Previous studies have shown that type 1 was more frequent in women and type 3 more frequent in men 2,4 . Type 3 can sometimes manifest as a subcutaneous scalp pseudotumor 5 .…”
mentioning
confidence: 87%
“…As shown in the study by Shahar et al, 8 the finding of osteophytes in the EOP by means of X-rays is increasingly frequent in daily clinical practice, with an incidence of 41%, affecting over 67% of men and 20% of women. Studies concerning cervical exostosis of the EOP are scarce and can be classified into radiological or anatomical studies.…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, the authors have frequently observed that this finding in the EOP is present in asymptomatic subjects, in line with existing evidence. 8 The ultrasound finding of this exostosis may indicate that this insertion area of the upper trapezius muscle is a subjective area of high or repetitive mechanical traction. Thus, the ultrasound assessment, always associated to the patient's clinical situation, allows us to evaluate and plan our physiotherapy treatment to include preventive postural measures that could aggravate this finding.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Alterations ofen theses (sites of ligament, tendon or capsule insertion) [1][2][3] have been suggested as markers of activity and pathology. Defined as bone reaction at sites of the insertions of tendons, ligaments and joint capsules [4,5], enthesial reaction has been variously considered to have a mechanical or inflammatory derivation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%